Acute effects of wearable thigh and shank loading on spatiotemporal and kinematic variables during maximum velocity sprinting. Issue 10 (26th November 2022) - Hurst, Oliver; Kilduff, Liam P.; Johnston, Michael; Cronin, John B.; Bezodis, Neil E.
ABSTRACT: Light wearable resistance is used in sprint training but the scientific evidence to guide its implementation is limited. This study investigated thigh and shank loading protocols which were matched based on the average increase in moment of inertia about the hip over a stride cycle. Seven university-level sprinters completed three counterbalanced conditions (unloaded, shank-loaded, thigh-loaded), and kinematic variables were measured between 30 and 40 m. Both thigh and shank loading led to small reductions in step velocity (mean change = −1.4% and −1.2%, respectively). This was due to small reductions in step frequency (−1.8%; −1.7%) because of small increases in contact time (+2.7%; +1.5%) in both conditions and a small increase in flight time (+2.0%) in the shank-loaded condition. Both conditions led to moderate increases in hip extension at toe-off (+2.7°; +1.4°), whilst thigh loading led to a small reduction in peak hip flexion angle during swing (−2.5°) and shank loading led to a small increase in peak biceps femoris muscle-tendon unit length (+0.4%). Thigh and shank loading can both be used to provide small reductions in sprint velocity, and each has specific overload effects which must be considered in the rationale for their implementation.